2016
DOI: 10.1007/s40519-016-0306-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of anthropometric factors, self-perception, and diet on weight misperception among young adolescents: a cross-sectional study

Abstract: These findings highlight that almost one-third of the participants had a weight misperception that was associated with several anthropometric, social, and lifestyle factors. Future intervention to prevent overweight and obesity should consider not only gender-specific differences, but also parental SES, perception, and satisfaction of body weight status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 48 publications
11
29
0
Order By: Relevance
“…This result clearly demonstrates the benefits of the Mediterranean diet, which has been previously related to a better state of general health, a lower body mass index, and a reduced risk of suffering from cardiovascular diseases [56]. Given that the nutritional patterns characteristic of the Mediterranean diet are associated with reduced obesity, reduced excess weight, and better general health, its consumption will markedly affect the self-concept, particularly the physical self-concept, reported by school children [57,58].…”
Section: Discussionsupporting
confidence: 61%
“…This result clearly demonstrates the benefits of the Mediterranean diet, which has been previously related to a better state of general health, a lower body mass index, and a reduced risk of suffering from cardiovascular diseases [56]. Given that the nutritional patterns characteristic of the Mediterranean diet are associated with reduced obesity, reduced excess weight, and better general health, its consumption will markedly affect the self-concept, particularly the physical self-concept, reported by school children [57,58].…”
Section: Discussionsupporting
confidence: 61%
“…Recent evidence suggests that the beneficial effects of the Mediterranean diet may depend on their content in polyphenols [ 52 , 53 , 54 , 55 ]. The Mediterranean dietary pattern has been associated with lower risk of cardio-metabolic disorders [ 56 , 57 , 58 , 59 , 60 , 61 ]. Previous results from this cohort showed a significant inverse association between higher adherence to this dietary pattern and hypertension [ 62 ]; however, another study showed that phenolic acid intake was associated in a non-linear manner to high adherence to the Mediterranean diet, suggesting that certain food sources of such polyphenol group not included in the classical paradigm of key features of the Mediterranean diet may provide beneficial action toward cardiovascular health [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stress perception was higher in males and females who perceived themselves as obese or thin. Compared to previous studies, adolescents stress was becoming obese (Chiang et al, 2019) and increasing the actual obesity is high (Hanlon et al, 2019) normal-weight perception, overweight perception, and underweight perception adolescents varied (Buscemi et al, 2018) and showed similar or different results from the reported as unrelated to personal BMI (Yayan and Çelebioğlu, 2018). Experiences of depression were more common in males who perceived themselves as thin and in females who perceived themselves as obese.…”
Section: Discussionmentioning
confidence: 54%
“…The proportion of the normal-weight adolescents who perceived themselves as thin was high in males and the proportion who perceived themselves as fat was high in females (Choi and Kim, 2017). In efforts for weight control, the proportion of efforts to lose weight was higher in females than males, and the proportion of efforts to maintain weight in the normal-weight group was lower than in the overweight and obese groups (Buscemi et al, 2018). But the efforts for the weight that it was higher in abnormal perception group (Hawkins et al, 2018).…”
Section: Discussionmentioning
confidence: 92%